2008
DOI: 10.1186/jbiol91
|View full text |Cite
|
Sign up to set email alerts
|

Aquaglyceroporins: ancient channels for metalloids

Abstract: A Aq qu ua ag gl ly yc ce er ro op po or ri in ns s: : a an nc ci ie en nt t c ch ha an nn ne el ls s f fo or r m me et ta al ll lo oi id ds s Hiranmoy Bhattacharjee, Rita Mukhopadhyay, Saravanamuthu Thiyagarajan and Barry P Rosen Address: Department of Biochemistry and Molecular Biology, Wayne State University, School of Medicine, Detroit, MI 48201, USA.Correspondence: Barry P Rosen. Email: brosen@med.wayne.edu Arsenic, a metalloid, is widely distributed in the Earth's crust and is toxic to all forms of life.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 16 publications
1
48
0
1
Order By: Relevance
“…In the present study, OsNIP3;2 and OsNIP3;3 were characterized as H 2 O 2 -permeable NIPs. As for arsenite transport, OsNIP3;3 and HvNIP1;2 were identified to show arsenite transport activity in addition to previously reported NIPs from rice, Arabidopsis, or Lotus japonicus (Ali et al 2009;Bhattacharjee et al 2008;Bienert et al 2008;Isayenkov and Maathuis 2008;Kamiya et al 2009;Ma et al 2008). Because OsNIP3;3 was found as an arsenite transporter, the effects of As(OH) 3 on the expression of OsNIP3;3 in rice plants were investigated (supplementary Figure S4).…”
Section: Arsenite Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, OsNIP3;2 and OsNIP3;3 were characterized as H 2 O 2 -permeable NIPs. As for arsenite transport, OsNIP3;3 and HvNIP1;2 were identified to show arsenite transport activity in addition to previously reported NIPs from rice, Arabidopsis, or Lotus japonicus (Ali et al 2009;Bhattacharjee et al 2008;Bienert et al 2008;Isayenkov and Maathuis 2008;Kamiya et al 2009;Ma et al 2008). Because OsNIP3;3 was found as an arsenite transporter, the effects of As(OH) 3 on the expression of OsNIP3;3 in rice plants were investigated (supplementary Figure S4).…”
Section: Arsenite Transportmentioning
confidence: 99%
“…Ma et al (2008) demonstrated that arsenite is transported via NIP aquaporins. Previously some rice NIPs (OsNIP1;1, OsNIP2;1= Lsi1, OsNIP2;2= Lsi6, OsNIP3;1, OsNIP3;2) were investigated as silicon (Si(OH) 4 ) or arsenite (As(OH) 3 ) transporters (Ali et al 2009;Bhattacharjee et al 2008;Bienert et al 2008;Ma et al 2008), but their water transport activities are not yet well understood. Novel OsNIP3;3 was characterized in the present study.…”
mentioning
confidence: 99%
“…Five major subgroups of aquaporins in plants are now recognized (Danielson and Johanson, 2008;Sade et al, 2009;Shelden et al, 2009). In particular, members of one of these subgroups, the nodulin-26-like intrinsic proteins (NIPs), were recently described as functional equivalents of aquaglyceroporins (Bhattacharjee et al, 2008). These channel pro-teins usually enable water transport but recent studies have demonstrated that they also facilitate transport of other small, uncharged solutes under physiological conditions including glycerol and lactic, boric (B), silicic (Si), arsenious (As), antimonious (Sb), and germanic (Ge) acids (Ma et al, 2006Takano et al, 2006;Choi and Roberts, 2007;Bienert et al, 2008;Chiba et al, 2008;Isayenkov and Maathuis, 2008;Tanaka et al, 2008;Kamiya et al, 2009;Mitani et al, 2009).…”
mentioning
confidence: 99%
“…Aquaporins share limited similarity with respect to sequence identity and differ in size, but the reported X-ray structures of aquaporins, such as bovine AQP0, human AQP1, E. coli AqpZ and GlpF, spinach SoPIP2;1, and Plasmodium falciparum PfAQP, show that these proteins share a conserved overall typical hourglass model (43)(44)(45). AQPs are assembled as homotetramers consisting of four independent monomers embedded in the lipid bilayer (46).…”
Section: Discussionmentioning
confidence: 99%